MAKKIYAH DAN MADANIYYAH: KAJIAN TEMATIK DAN IMPLIKASINYA DALAM KEHIDUPAN UMAT ISLAM - Neng Sufia; Abu Anwar (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2025)
This study explores the thematic characteristics of Makkiyah and Madaniyyah verses in the Qur'an and their relevance in modern life. Makkiyah verses, which were revealed before the Prophet Muhammad's migration, emphasize monotheism, morality, and individual faith. Meanwhile, Madaniyyah verses, which were revealed after the migration, focus on law, social, and politics in building a just society. Qualitative approach based on literature review, thematic analysis of the language style, themes, objectives of each group of verses. The results show that Makkiyah verses instill universal values ​​that are relevant throughout time, such as social justice and the relationship between humans and God. Madaniyyah verses offer specific guidance in social and legal aspects, reflecting Islam's flexibility in responding to the needs of the times. The implications of this study highlight the importance of a deep understanding of both groups of verses to address modern challenges, including pluralism, globalization, and the crisis of morality. This study contributes to enriching the understanding of Muslims about the Qur'an as a guide to life that is applicable in various contexts, both in education, preaching, and public policy. Thus, this study supports the implementation of the teachings of the Qur'an holistically to build a harmonious and inclusive society.